Dinamika Universalitas Dan Relativisme Dalam Hak Asasi Manusia - Moh. Khoirul Fatih (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2018)
The influence of Western culture has been recognized as very decisive towards the existence of the Universal Declaration of Human Rights in 1948, and the formulation and stipulations of international human rights that cannot be denied. Awareness of this has led to ideological conflicts in international scale human rights discourse. The conflict includes challenges to the application of universal human rights and rejection of the diagnosis that human rights norms can be understood as a standard that knows no time limits and differences in nationality throughout the world. The dynamics of universality and relativism around Ham seen from the perspective of conflict resolution produce several views including that the dynamics of universality and relativism in human rights begin when there are many incompatibility of human rights norms with socio-cultural cultural societies. The resolution of the problems related to human rights above is dialogue. Dialogue can be the best way if each party accepts openly the issues related to human rights norms, which are considered to be incompatible with cultural culture and can eventually be resolved.